2019
DOI: 10.1002/adma.201904816
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Segregation Boosting High‐Voltage Cyclability of Layered Cathode for Sodium Ion Batteries

Abstract: PIBs). [7,8] Either in the form of O3 structure, P2 structure or other else structures, their common similarity is the layer by layer stacking sequence of transition metal ions, oxygen ions, and alkaline ions. [9,10] Such a layered structure not only enables high-specific capacity but also favors the fast migration of alkaline ions due to the unique 2D diffusion pathway. Thus, layer structured LiCoO 2 , ternary NMC (LiNi x Mn y Co z O 2 , x + y + z = 1), and NCA (LiNi 0.85 Co 0.1 Al 0.05 O 2 ) have achieved gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 51 publications
7
64
0
Order By: Relevance
“…The cycling performance of P2‐NNMO‐PMCs is demonstrated via long‐term cycling measurement at 2 C and 5 C, as shown in Figure 2D and E, respectively. As depicted, it can deliver an initial specific capacity of 83.2 mAh g −1 with a capacity retention of 98.3 % after 300 cycles and could achieve a capacity retention of 94.6 % after cycling 1500 cycles at 5 C. The cycling performance of P2‐NNMO‐PMCs is superior when compared with other reported layered oxide cathodes (Table S3) [19,24, 43–50] . The calculated energy densities for P2‐NNMO‐PMCs electrode also exhibit an overwhelming advantage compared to P2‐NNMO‐B (Figure S11), which could be critical for full cell device.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…The cycling performance of P2‐NNMO‐PMCs is demonstrated via long‐term cycling measurement at 2 C and 5 C, as shown in Figure 2D and E, respectively. As depicted, it can deliver an initial specific capacity of 83.2 mAh g −1 with a capacity retention of 98.3 % after 300 cycles and could achieve a capacity retention of 94.6 % after cycling 1500 cycles at 5 C. The cycling performance of P2‐NNMO‐PMCs is superior when compared with other reported layered oxide cathodes (Table S3) [19,24, 43–50] . The calculated energy densities for P2‐NNMO‐PMCs electrode also exhibit an overwhelming advantage compared to P2‐NNMO‐B (Figure S11), which could be critical for full cell device.…”
Section: Figurementioning
confidence: 85%
“…As depicted, it can deliver an initial specific capacity of 83.2 mAh g À 1 with a capacity retention of 98.3 % after 300 cycles and could achieve a capacity retention of 94.6 % after cycling 1500 cycles at 5 C. The cycling performance of P2-NNMO-PMCs is superior when compared with other reported layered oxide cathodes (Table S3). [19,24,[43][44][45][46][47][48][49][50] The calculated energy densities for P2-NNMO-PMCs electrode also exhibit an overwhelming advantage compared to P2-NNMO-B ( Figure S11), which could be critical for full cell device. In addition, the testing potential range is further extended to 1.5-4.0 V to further investigate the effect of structural design on our P2-NNMO-PMCs.…”
mentioning
confidence: 99%
“…[ 7–10 ] As one type of promising cathode materials for NIBs, layered transition metal oxides Na x TMO 2 (0 < x ≤ 1; TM = Fe, Co, Ni, and Mn) have been intensively investigated because of possessing high capacity, appropriate operating potentials, and facile synthesis. [ 11–14 ] Typically, Na x TMO 2 is classified into two main types of phases: O3 and P2, [ 15–17 ] where O represents the octahedral environment for Na site, P represents the prismatic environment for Na site, and the number 2 or 3 means the minimum number of transition metal layers in a single cell unit. O3‐phase cathode with sufficient Na content delivers a high reversible capacity, however, suffers from the limited cycle stability and poor rate capability owing to one and more complex phase transformations resulting from the Na ions diffuse through the face‐shared tetrahedral sites (intermediate site) during sodiation/desodiation process.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, recent research results indicate that TM accidentally occupied in the sodium layer does improve the structural stability of the layered cathode. [8] Our recent work revealed that part of the TM irreversibly occupied from the TM layer to the Na layer during the first de-sodiation process,a nd the unfavorable phase transformation also disappeared during the subsequent sodiation and de-sodiation process. [8b] But, it should be noted that too much TM in sodium layer would severely block the diffusion of sodiumions,w hile insufficient pinned TM would not form the rocksteady structure.T herefore,i tr emains ah uge challenge to intelligently control the pinned TM in sodium layer to enhance the thermodynamic stability without affecting the normal Na-ion diffusion.…”
Section: Introductionmentioning
confidence: 99%